Invasive streptococcus pneumoniae infection in the hip joint and thigh muscle group of an adult diagnosed by Q-mNGS: a case report - Su, Dongming; Ni, Tu; Yu, Xiu-lei (Journal of the Pakistan Medical Association, 2026)
Joint infections and myositis due to S. pneumoniae are rare. We report the case of a young adult male presenting with right hip joint infection complicated by thigh muscle abscess, successfully treated by surgical debridement, drainage tube placement, and aggressive antimicrobial therapy. A 38-year-old male presented with right buttock and thigh swelling, pain, night sweats, and limited mobility for 45 days. Imaging examination indicated soft tissue infection around the right hip joint with abscess formation. Quantitative meta-genomic next-generation sequencing (Q-mNGS) of joint fluid confirmed S. pneumoniae as the pathogen. Surgical intervention was performed due to lack of significant improvement after six days of anti-inflammatory therapy. The patient recovered well post-operatively and was discharged with medication after a total hospital stay of 31 days. This case highlights the importance of considering S. pneumoniae as a potential pathogen in joint and soft tissue infections in adults. Keywords: Streptococcus pneumoniae, Hip joint infection, Muscle abscess, Q-mNGS.